Uji Aktivitas Antihiperlipidemia Ekstrak Etanol Daun Kalakai (Stenochlaena Palutris (Burm.F.) Bedd Pada Tikus Putih Wistar Secara In vivo - Rabiatul Adawiyah (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
Kalakai plants or ferns are plants whose habitat is in swamps, including plants that have been consumed for generations as food, sothat kalakai has great potential as a traditional medicine typical of Kalimantan. Hyperlipidemia is a disorder characterized by increased levels of lipids (fats) in the blood, especially cholesterol and triglycerides. The purpose of the study was to determine the antihyperlipidemic effect and to find out at what dose of kalakai leaf extract could reduce lipid levelss in wistar white rats in vivo. The method used is to test the antihyperlipidemic activity method by giving treatment to experimental animals with normal control test groups, positive control, negative control, testing dose of 100 mg/KgBB, testing dose 200 mg/KgBB and testing dose 400mg/KgBB using a UV-VIS spectrophotometer. The result obtained for the positive control that the total cholesterol level was 36,4 ± 1,85 and for triglycerides of 33± 3,03 at a total cholesterol dose of 100 mg/KgBB of 69,4 ± 3,00; a dose of 200 mg/KgBB of 56,6 ± 2,24; the dose of 400 mg/KgBB 40± 1,89 while for triglyceride levels the dose of 100 mg/KgBB was 63,4 ± 2,57; a dose of 200 mg/KgBB of 51,8 ± 1,32; and a dose of 400 mg/KgBB of 38 ± 2,00. So the conclusion is that the kalakai leaf extract at a dose of 400mg/KgBB has an antihyperlipidemic effect and is able to reduce lipid levels in wistar white rats in vivo.